Synthesis and fluorescence studies of selected N-aryl-2-aminoquinolines: Effect of hydrogen bonding, substituents and ESIPT on their fluorescence quantum yields - Hisham, Shameer; Tajuddin, Hairul Anuar; Chee, Chin Fei; Hasan, Zainal Abidin; Abdullah, Zanariah (Elsevier, 2019)
N-aryl-2-aminoquinolines have been widely synthesised and used in biological applications. However, their luminescence properties have not been studied in detail. Herein a series of N-aryl-2-aminoquinolines was synthesised from substitution reaction between 2-chloroquinoline and anilines with different substituent groups gave sufficient yield from 72–90%. The fluorescence behaviour was investigated in toluene, ethyl acetate and ethanol. The result shows that fluorescence quantum yield of N-aryl-2-aminoquinolines was the highest in toluene, followed by in ethyl acetate and the lowest in ethanol. Quenched emission observed in ethanol is caused by site-specific fluorophore-solvent hydrogen bonding interactions, inducing deactivation of the quinolinyl ring system. The bell-shaped Hammett plot of various substituted compounds suggested that both strong electron donating and electron withdrawing groups caused significant quenching in the fluorescence quantum yields. Therefore, most types of substituent groups on the phenyl moiety, hydrogen bonding between the fluorophore and solvent, and excited-state intramolecular proton transfer (ESIPT) were found as crucial contributors to fluorescence quenching of N-aryl-2-aminoquinolines.